Processing Durian Skin Into Compost Using Enumeration Machine Technology in Sungai Raya Village - Erna Frida; Bukit, Ferry Rahmat Astianta; Siregar, Achmad Husein (Talenta Publisher, 2022)
Dairi Regency is the largest durian fruit producer in North Sumatra Province with a production of 23 thousand tons per year. One of the largest durian-producing villages in Dairi Regency is Sungai Raya Village. The estimated volume of durian skin waste produced in North Sumatra is 332,712 tons of durian skin per year, this can be seen from the large amount of durian skin waste that accumulates on the side of the road, in rivers, and farmers' gardens. Given the large volume of durian skin, it takes an effort to process durian skin waste into compost that can be used by farmers and can improve the welfare of farmers. The solution for processing durian skin is to build a community-based processing unit for processing durian skin into community-based compost by involving farmer groups. To carry out efforts to manage durian skin waste, a simple tool is needed that functions as a durian skin chopper as a basic material for compost. From the results of the durian skin counting and the dissemination of fertilizer making, farmer groups and the community have been able to make fertilizer from durian skin so that it can increase the income of the population.